A General Equilibrium Model of Changing Risk Premia: Theory and Tests - Bossaerts, Peter; Green, Richard C. (Review of Financial Studies, 1989)
We derive and test a dynamic discrete-time model of asset returns. Both the risks of individual securities and equilibrium risk premia change predictably in the model, but these changes can be attributed to movements in the returns and prices of only two well-diversified portfolios. Any other components of returns should be unpredictable. Using the generalized method of moments, the model is estimated and tested on portfolios of equities. We find the data supportive of the model’s restrictions, even when instruments designed to capture the January effect are employed.